Leonardo e il ghiaccio: l’interesse di Leonardo per l’arte fiamminga e viceversa - Forcellino, Maria (Incontri. Rivista europea di studi italiani, 2020)
Leonardo and ice: Leonardo’s interest for the Flemish art and vice versa The aim of the article is to underscore the importance of cultural exchange: on the one hand Leonardo’s knowledge of Flemish oil painting techniques at the beginning of his career made it possible for him to improve his style; on the other hand his influence extended in an early stage to the Low Countries, and concerned thematical choices. The first part of the article focuses on the period in which Leonardo, during his apprenticeship in the workshop of Andrea del Verrocchio, became aware of the significance of the new oil technique, which had been imported in Florence due to economic contacts with Bruges in the fifteenth century and the role of Florentine families such as the Medici, the Portinari and the Pagagnotti. The possibilities of the new oil painting technique were explored in Florence in the workshops of Verrocchio and the Pollaiolo brothers. A signature in the Codice Atlantico testifies that Leonardo himself was acquainted with members of the Portinari family, active in Bruges. Knowledge of Flemish art became essential in technical and formal aspects of his first female portrait, the Portrait of Ginevra Benci, which had been ordered by Bernardo Bembo as a pendant to his own portrait, painted by Hans Memling during his mission in Bruges as an ambassador to the Venetian Republic. The second part intends to invert the focus and to study Leonardo’s influence on Flemish art by presenting several paintings on the subject of Jesus and Saint John embracing. This iconographic subject originates from a composition, once in the royal collection in Mechelen, of Leonardo’s pupil, Marco D’Oggiono. The Flemish painter Joos van Cleve probably saw it and started to produce many paintings on this subject in his workshop in Antwerp. These works were so successful that over fifteen of them survive in different collections in Europe, and constitute a good example of Flemish artists’ interest in Leonardo’s art.